바이오가스 생산시설의 비용·편익 사례 분석 - 윤영만 (한국농촌경제연구원, 2012)
This study conducted a case study analyzing the cost and benefits of biogas plants that use livestock manure to produce biogas. The purpose was to review the possibility of expanding the facilities across the country. According to the analysis results, it was found that in most cases economic viability would be very low if the revenue is earned through the selling of surplus electricity only. If we consider the sales revenue from surplus power as the direct benefit(Scenario 1), the compensation rate would be 24.8% of total facility cost. However, in Scenario 2 where we consider private investment as the only cost, the compensation rate would be 34.0% of the total cost. It was found that if indirect benefit is taken into account, only the biogas facility in Jeju Island would generate an economic benefit of 381 won/㎥. In the cost analysis of private investment, it was estimated that the economic benefit of the biogas plants would be 2,565~4,809 won/㎥, that is, excluding two plants in Suncheon and Changnyeong that are built with private investment only and another two plants in Anseong that are built for experimental purpose only. Therefore, in order to improve the economic viability of manure biogas plants, government support is needed more than anything else to share the initial facility cost.
Keywords: 바이오가스 생산시설; 신재생에너지; 비용-편익; 청정에너지; biogas plant; new and renewable energy; cost-benefit; clean energy